Chronic myeloid leukemia in case of Klinefelter syndrome - Chennuri, Vasundhara (Medknow Publications & Media Pvt Ltd, 2014)
Klinefelter syndrome (KS) is a sex chromosome disorder and has been reported to be associated with increased risk for malignancies. We report a 22-year-old male patient who was diagnosed to have chronic myeloid leukemia in chronic phase. Bone marrow cytogenetic examination revealed karyotype 47, XXY, t (9; 22)(q34, q11) suggestive of KS with presence of Philadelphia chromosome. The patient was treated with oral imatinib mesylate (400 mg/day). Complete hematological response was achieved after 2 months of therapy. The bcr-abl/abl transcript percentage measured from peripheral blood at baseline, 1 and 2 years after imatinib were 97%, 1.99%, 0.007%, respectively. He remains in complete hematological and major molecular remission after 2 years of continued imatinib therapy.